2013
DOI: 10.2139/ssrn.2229271
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Enterprise Risk Management Implementation on the Firm Value of European Companies

Abstract: We aim to investigate the impact of the adoption of an Enterprise Risk Management (ERM) system on the enterprise value and to discover which are the determinants of this choice. Several economic actors have decided to face the current economic and financial complexity shifting from a Traditional silo-based Risk Management approach (TRM) to a more comprehensive one, the so called Enterprise Risk Management (ERM). Some academics have tried to investigate the effects of the ERM implementation on firm value, mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 23 publications
6
36
0
5
Order By: Relevance
“…The results of this research led us to identify the level of risk culture as a factor which has a positive, strong and significant impact on financial performance within manufacturing SMEs in Cameroon and others factors have a negative but significant impact. These results are in conformity with Giorgio et al, (2013) [15]who found that the management of risks has a positive impact on the value of European companies. This result confirms also the assertion of Green and Jennings-Mares (2008) which stipulates that the most important element in risk management throughout firms is a cultivation of a consistent risk culture.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this research led us to identify the level of risk culture as a factor which has a positive, strong and significant impact on financial performance within manufacturing SMEs in Cameroon and others factors have a negative but significant impact. These results are in conformity with Giorgio et al, (2013) [15]who found that the management of risks has a positive impact on the value of European companies. This result confirms also the assertion of Green and Jennings-Mares (2008) which stipulates that the most important element in risk management throughout firms is a cultivation of a consistent risk culture.…”
Section: Discussionsupporting
confidence: 92%
“…The results show that an increase in the level of ERM implementation in companies positively contributes to the value of the companies. Giorgio and al., (2013) [15]as for him examines the impact of adoption risk management on the value of company and on the determinants of the choice of risk management. Based on a sample of 200 companies in the financial and non-financial sector; their results showed that risk management has a positive impact on the value of the European companies.…”
Section: Significant Relationship Between Erm Implementation and Firmmentioning
confidence: 99%
“…Untuk menghadapi keadaan yang ada, perusahaan perlu menyediakan perangkat manajemen yang dapat mengelola risiko (Widjaya & Sugiarti, 2013). Bertinetti et al (2013), Hoyt and Liebenberg (2011) Hoyt and Lienbenberg (2011), ), Li et al (2014).menghubungkan antara Enterprise Risk Management (ERM) dengan nilai perusahaan menemukan bahwa penerapan ERM memiliki dampak signifikan positif pada nilai perusahaan. Hasil empiris mendukung bahwa ERM akan meningkatkan nilai perusahaan sebesar 3,6%-17% lebih tinggi dari perusahaan yang tidak menerapkan ERM.…”
Section: Pendahuluanunclassified
“…Hal tersebut berkaitan dengan pernyataan Hyot dan Lienberg 2011bahwa pengelolaan risiko perusahaan adalah bagian dari strategi bisnis secara keseluruhan dan dimaksudkan untuk berkontribusi melindungi dan meningkatkan nilai pemegang saham. Beberapa penelitian juga telah membuktikan bahwa pengungkapan ERM memiliki pengaruh positif terhadap nilai perusahaan seperti penelitian Bertinetti et al, (2013) Penelitian ini menggunakan variabel terikat berupa nilai perusahaanyang diartikan sebagai total penjumlahan nilai pasar utang dengan nilai pasar saham (Modigliani dan Miller, 1963 Nilai tolerance dari hasil uji multikolonieritas menunjukan tidak ada variabel bebas dan variabel kontrol yang memiliki nilai tolerance kurang dari 0,10 (10%). Begitu juga dengan nilai Variance Inflation Factor (VIF) yang menunjukan tidak ada satu variabel pun yang memiliki nilai VIF lebih dari 10.…”
Section: Pendahuluanunclassified